Pengaruh Penggunaan Reward Terhadap Kepercayaan Diri Peserta Didik Pada Mata Pelajaran Ips Di Smp Negeri 11 Solok Selatan: The Effect of Using Rewards on Students' Self-Confidence in Social Sciences Subjects at SMP Negeri 11 Solok Selatan - Mardillah, Whike; Yasin, Faishal; Harisnawati, Harisnawati (Universitas Pahlawan Tuanku Tambusai, 2025)
This research was motivated by the low self-confidence of students and students were not active in participating in learning, students tended not to raise their hands and students tended to be silent, as evidenced by subject grades that were below average. Students are not enthusiastic about learning and are less responsive, resulting in low levels of student confidence. The type of research used is quantitative descriptive research. The influence of the use of rewards on students self- confidence in social studies subjects at SMP Negeri 11 Solok Selatan is based on the results of the research hypothesis with a large significance of 0.05 (a=5%) or (0.000 <0.05), which means that this data has a significant influence. So the reward use variable has a positive and significant effect on students' self-confidence in social studies subjects at SMP Negeri 11 Solok Selatan. The results of this research were dominated by female respondents at 50.7%. The contribution of the use of rewards to students' self-confidence in social studies subjects at SMP Negeri 11 Solok Selatan is 20.3%. Based on the research that has been carried out, this means that the use of rewards has a big role in increasing students' self-confidence, so that the goals of social studies learning at SMP Negeri 11 Solok Selatan can be achieved and get satisfactory resultsSo the reward use variable has a positive and significant effect on students' self-confidence in social studies subjects at SMP Negeri 11 Solok Selatan. The results of this research were dominated by female respondents at 50.7%. The contribution of the use of rewards to students' self-confidence in social studies subjects at SMP Negeri 11 Solok Selatan is 20.3%. Based on the research that has been carried out, this means that the use of rewards has a big role in increasing students self-confidence, so that the goals of social studies learning at SMP Negeri 11 Solok Selatan can be achieved and get satisfactory results. In education, a reward is a prize obtained by students' strong efforts through learning. Based on the research results, it can be seen that students are more enthusiastic and motivated to carry out learning activities by implementing rewards in learning. This is in line with several previous studies which stated that there is an influence of rewards on students' self-